A review of processing techniques for Fe-Ni soft magnetic materials - Ali, M. (Taylor and Francis Inc., 2019)
This article reviews the available literature published to date on the development of Fe-Ni soft magnetic materials. The nickel content varies from 2 to 90 and the properties change with composition, accordingly. These are the imperative materials for various electromagnetic applications. The soft magnetic materials are well established, and a lot of research work has been carried out via conventional and advanced processing techniques. In this article, the processing techniques of powder injection molding, powder metallurgy, mechanical alloying, spark plasma sintering, solution combustion synthesis, and selective laser melting are discussed and highlighted. The effect of processing parameters on densification, microstructure, and magnetic properties is critically analyzed and summarized in tabulated form at the end of each section. In addition to that, strong and weak aspects of the microstructure-property relationship are discussed in a systemic way. Lastly, future recommendations and research work need attention is also included at the end. Â© 2019, Â© 2019 Taylor & Francis.